AUTOMATION OF FINANCIAL ACCOUNTING IN CONSTRUCTION COMPANIES: PROSPECTS AND RISKS - Nurzhan Bakhadurov (Modern American Journals, 2025)
The article considers the issues of automation of financial accounting in construction companies in the context of digital transformation of the economy. The theoretical foundations of digitalization of accounting processes are defined, modern technologies are analyzed, including integrated ERP-class systems, cloud solutions, artificial intelligence, blockchain and robotization of routine operations. Based on practical examples of the implementation of automated systems in Russian and foreign construction organizations, the key advantages of digitalization are identified, including increased transparency of financial flows, reduced costs, improved control over the use of resources and stronger trust on the part of investors and customers. At the same time, the risks associated with high implementation costs, staff resistance, cybersecurity threats and difficulties in integrating various systems are identified. Ways to minimize these risks are proposed, including planning, employee training, ensuring information security, using scalable solutions and applying analytical tools. It is concluded that automation of financial accounting is a strategic direction for the development of construction companies, contributing to their sustainable growth and increased competitiveness.